STUDY OF TEOLINGUISTICS AND TEOLINGUISTIC UNITS IN UZBEKISTANI - Rakhmonova Nodirakhon Mukhammadjonovna (Bright Mind Publishing, 2025)
Research in the field of theolinguistics and theolinguistic units in the Uzbek language is gaining attention as one of the new directions in linguistics. The term theolinguistics is aimed at studying the relationship between language and its various forms, styles, and contexts, allowing for a deep analysis of the social, cultural, and communicative functions of language. This field is closely related not only to linguistics, but also to such disciplines as anthropology, sociology, and psychology, and studies the role of language in society and how it is formed in a social context.
Keywords: Theolinguistic units, theolinguistics, language, linguistics, society, relationships, communicative skills, terms.